The Concept of Kawruh Jiwa and Pamomong in The Perspective of Ki Ageng Suryomentaram - Subur Subur; Chubbi Syauqi (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
The purpose of this study is to describe one of the local wisdom or Javanese traditions, namely the concept of kawruh jiwa and pamomong in the perspective of Ki Ageng Suryomentaram, one of whose views is related to education. This study used a qualitative approach with a descriptive method. The data was collected through library research and literature searches related to the concept of kawruh jiwa and pamomong from Ki Ageng. The result of the study showed that the concept of kawruh jiwa and pamomong developed by Ki Ageng is cohesion that the Javanese people must-have. Both became the main philosophy of life for the Javanese. Kawruh jiwa is an aspect of feeling or roso so that humans understand themselves completely. Meanwhile, the concept of pamomong becomes an important principle for parents and educators in educating children or students. It is because pamomong is teaching to understand the right thing and think well. This means that kawruh jiwa and pamomong complete each other. Before becoming a good educator, everyone must understand themselves (kawruh jiwa).